Kinetic Study of Application of ZnO as a Photocatalyst in Heterogeneous Medium - J. J. Vora; S. K. Chauhan; K. C. Parmar; S. B. Vasava; S. Sharma; L. S. Bhutadiya (E-Journal of Chemistry)
The photocatalytic degradation of 2,4-dinitrophenol over ZnO was carried out in the presence of light. Control experiments were carried out. The photocatalytic degradation of 2,4-dinitrophenol was observed spectro-photmerically. The various parameters like concentrations of substrate, pH, amounts and band gaps of semiconductor, impact of light intensity, sensitizers and radical quenchers affected the kinetics of the degradation process. A probable mechanism for this process has been proposed.